Foguetes de garrafa pet, uma proposta experimental para trabalhar as leis de Newton no Ensino Médio - Casagrande Junior, Sergio Antonio (2020)
Physics classes worked traditionally have been shown inefficient for the scientific literacy of young people at high school. The worked experimentation in a non-literal, non-random, constructivist and with very specific objectives can help to change this retrospect, sometimes, of students' lack of interest in sciences. The search for methodological innovations for the teacher to motivate students to interest in scientific knowledge was fundamental for this research. Starting on a theoretical framework based on Ausubel's Theory of Meaningful Learning, this qualitative research sought to improve high school physics classes, that the Newton's Laws were proved in practice with the construction of a pressure rocket with PET bottle, with the aid of a virtual projectile launch simulator and a data analysis program. The results were very satisfactory and the students' involvement was surprising. The use of the Phet colorado simulator before the rocket experiment helped to understand ideal and not ideas situations, for example, with air resistance. In comparing the results obtained in the pre-test with the post-test, it can be observed that the concepts of inertia, resulting force and principle of action and reaction had a significant evolution on the Physics knowledge by the students.